Sosialisasi Retribusi Pasar pada Pasar Ikan Lamongan - Tri Winarsih; Rina Sulistyowati; Ida Fitriyah (Pusat Riset dan Inovasi Nasional, 2021)
In the implementation of regional development, the active role of the community in regional planning institutions needs to be increased and coordinated with each other in order to achieve faster and more targeted development. The regional autonomy implemented aims to assist the implementation of the central government, especially in providing services to the community and implementing development programs so that there is a need for efforts to increase regional income from local revenue (PAD). One of the financial sources obtained comes from retribution. Awareness of the obligation to charge fees is often related to willingness and compliance in exercising the rights and obligations of fees in accordance with applicable regulations, especially regarding community knowledge, level of education, and the applicable system. Lamongan Regency is one of the areas with abundant resources in the form of fishery products. The Lamongan Fish Market is a form of government service to business actors in carrying out fishery product transactions. Thus, socialization regarding fees at the Lamongan Fish Market needs to be carried out in order to create awareness of mandatory fees for the sake of development progress in Lamongan Regency.